The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/neu0000094
|View full text |Cite
|
Sign up to set email alerts
|

Visual-spatial abilities relate to mathematics achievement in children with heavy prenatal alcohol exposure.

Abstract: Objective The current study examined the relationship between mathematics and attention, working memory, and visual memory in children with heavy prenatal alcohol exposure and controls. Method Fifty-six children (29 AE, 27 CON) were administered measures of global mathematics achievement (WRAT-3 Arithmetic & WISC-III Written Arithmetic), attention, (WISC-III Digit Span forward and Spatial Span forward), working memory (WISC-III Digit Span backward and Spatial Span backward), and visual memory (CANTAB Spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Our results are consistent with previous literature which found that school-age children who have been prenatally exposed to alcohol perform significantly lower than typically developing peers across academic domains (Streissguth et al, 1990, Howell et al, 2006, O’Leary et al, 2013, Glass et al, 2015, Crocker et al, 2015). Children with prenatal exposure to alcohol demonstrated impairments on higher order mathematical reasoning as well as lower order functions such as basic numerical processing, basic calculations, proximity judgment, and cognitive estimation (Coles et al, 2009, Lebel et al, 2010, Crocker et al, 2015, Kopera-Frye et al, 1996, Meintjes et al, 2010; Jacboson et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous literature which found that school-age children who have been prenatally exposed to alcohol perform significantly lower than typically developing peers across academic domains (Streissguth et al, 1990, Howell et al, 2006, O’Leary et al, 2013, Glass et al, 2015, Crocker et al, 2015). Children with prenatal exposure to alcohol demonstrated impairments on higher order mathematical reasoning as well as lower order functions such as basic numerical processing, basic calculations, proximity judgment, and cognitive estimation (Coles et al, 2009, Lebel et al, 2010, Crocker et al, 2015, Kopera-Frye et al, 1996, Meintjes et al, 2010; Jacboson et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Of note, the newly updated clinical guidelines for diagnosing fetal alcohol spectrum disorders include specific learning impairment (across academic domains) as satisfying the criteria for the neurobehavioral impairment in the diagnoses (Hoyme et al, 2016). However, poor performance on math has emerged as an area of selective vulnerability for children with prenatal alcohol exposure (Coles et al, 2009, Jacobson et al, 2011, Lebel et al, 2010, Crocker et al, 2015, Howell et al, 2006, Kerns et al, 1997, Kopera-Frye et al, 1996) with less research on other academic domains (O’Leary et al, 2013, Glass et al, 2015, Streissguth et al, 1994a, Howell et al, 2006). Howell et al, (2006), compared alcohol-exposed children with and without dysmorphology to children in special education classes and those with similar socioeconomic backgrounds, and found that all children performed one to two standard deviations below the normative mean.…”
Section: Introductionmentioning
confidence: 99%
“…Given that these factors are associated with reduced academic achievement and higher rates of learning disabilities, it is not surprising that children with histories of prenatal alcohol exposure experience higher rates of poor educational outcomes (Streissguth, 1992), including deficits in all three domains of academic achievement: reading, writing, and math (Jirikowic, Carmichael Olson, & Kartin, 2008). Despite an emphasis on describing and treating mathematics deficits (Coles, Kable, & Taddeo, 2009; Crocker, Riley, & Mattson, in press), verbal academic difficulties have not been comprehensively examined. Spelling ability is understudied in this population, despite the view that “spelling correctly is perhaps one of the most valued, yet difficult skills in written communication” (Wanzek et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In developmental disorders, academic screening tests like the Wide Range Achievement Test (WRAT; Jastak, 1946; Jastak & Jastak, 1965, 1976, 1978; Jastak & Wilkinson, 1984; Wilkinson, 1993) are commonly used as a basic index of academic proficiency, which is especially important in terms of calibrating demographic comparisons between those with developmental disorder and typically developing controls. Such academic screening methods have been employed in studies on children with autism spectrum disorder (Luiselli, Campbell, Cannon, Dipietro, Ellis, Taras, et al ., 2001), low birth-weight (O’Keeffe, O’Callaghan, Williams, Najman, & Bor, 2003), sleep disorders (Bourke, Anderson, Yang, Jackman, Killedar, Nixon, et al ., 2011), Huntington’s disease (O’Rourke, Adams, Duff, Byars, Nopoulos, Paulsen, et al ., 2011), cognitive impairment (Ahl, Beiser, Seshadri, Auerbach, Wolf, & Au, 2013), epilepsy (Berg, Caplan, Baca, & Vickrey, 2013), heavy prenatal alcohol exposure (Crocker, Riley, & Mattson, 2015), and children who have been abused (Mills, Alati, O’Callaghan, Najman, Williams, Bor, et al ., 2011). Also, parental or other informant information about a child’s academic ability is typically estimated by survey instruments, and having an actual ability measure provides external confirmation for parental and informant reports of academic skills (Arciuli, Stevens, Trembath, & Simpson, 2013).…”
mentioning
confidence: 99%
“…As the fourth edition of the WRAT (WRAT–4; Wilkinson & Robertson, 2006) was not available at the outset of the study, the WRAT–3 was used for the study’s duration in order to maintain data homogeneity. Although the WRAT–4 has been available since 2006, the WRAT–3 continues to be used in research involving children (Berg, et al ., 2013; McNally, Bangert, Dietrich, Nuss, Rusin, Wright, et al ., 2013; Crocker, et al ., 2015) and adults (O’Rourke, et al ., 2011; Light, Swerdlow, Rissling, Radant, Sugar, Sprock, et al ., 2012). This continued use of the WRAT–3 supports the purpose of the current study.…”
mentioning
confidence: 99%